PENERAPAN STRATEGI PEMBELAJARAN QUESTION STUDENT HAVE (QSH) PADA MATERI SISTEM PERTAHANAN TUBUH UNTUK MENGETAHUI HASIL BELAJAR PESERTA DIDIK - Intan Nisa; Ara Hidayat; Meti Maspupah (Jurnal BIOEDUIN : Program Studi Pendidikan Biologi, 2015)
The study was based on a preliminary study at the school, which shows the lack of a wareness of the students to learn and repeat the subject matter presented so that the material obtained is easily for gotten, in addition regarded biology lessonfull of scientific studies that are difficult to pronounce and in memorized. Problems a rising from the necessary existence of the selection of appropriate learning strategies. One of the alternative learning strategies that have Student Question (QSH). The purpose of the study to determine the learning out comes of students in the material of the body's defense system by using strategies have student Question (QSH). This study uses the Pre-Experimental Design using the class as a class experiment(treatment). The populationin this study are all students of class XI Science SMAN 1.The sampling technique used is the purposive sampling technique. Retrieved sample of class XI Science 1 with a sample size of 24 students. Data processing is performed by the comparative analysis of the normality test, Z test, and find the value of N-Gain. Cognitive learning out comes of students achieved an average of 80.54 with KKM 75. Further analysis of the data, based on the calculation of the expected frequency table for thenormality teston the pretest and posttest pretest values obtained x2 count: 2.8893 and x2 countand posttest: 2.4180. When compared with the table valuex2 = 7.81 mean pretest and posttest data is normally distributed. The next step is to test the Z, then the values obtained posttest = Z count: -0.56 and Z tables: -1.65. In this case the Zcount > -Z table, then Ho is rejected and Ha accepted. And N-Gain value in this study is 0:56 in medium category, thus it can be said that the implementation of student learning strategies have Question (QSH) can improve the learning out comes of students.